2010
DOI: 10.1111/j.1365-3040.2010.02228.x
|View full text |Cite
|
Sign up to set email alerts
|

An analytical model of non‐photorespiratory CO2 release in the light and dark in leaves of C3 species based on stoichiometric flux balance

Abstract: Leaf respiration continues in the light but at a reduced rate. This inhibition is highly variable, and the mechanisms are poorly known, partly due to the lack of a formal model that can generate testable hypotheses. We derived an analytical model for non-photorespiratory CO2 release by solving steady-state supply/demand equations for ATP, NADH and NADPH, coupled to a widely used photosynthesis model. We used this model to evaluate causes for suppression of respiration by light. The model agrees with many obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 87 publications
(169 reference statements)
3
61
1
Order By: Relevance
“…These studies usually examined photosynthetic performance in response to short‐term or long‐term changes in irradiance, and while they have generally reported only small perturbations in photosynthesis as a result of the change in AOX amount, they are nonetheless a body of work supporting the idea that this unique respiratory pathway may have a specific role in the photosynthesizing cell (Noguchi and Yoshida ). These finding are further supported by recent computational modelling studies of plant metabolism, some of which predict an increased contribution of AOX to respiration with increasing irradiance (Buckley and Adams , Cheung et al , Nikoloski et al ). Interestingly, a role of AOX in optimizing photosynthesis at high irradiance was also recently established for the diatom Phaeodactylum tricornutum , using an AOX knockdown approach (Bailleul et al ), and knockdown of AOX in soybean has also been shown to perturb photosynthesis (Chai et al ).…”
Section: Introductionsupporting
confidence: 62%
“…These studies usually examined photosynthetic performance in response to short‐term or long‐term changes in irradiance, and while they have generally reported only small perturbations in photosynthesis as a result of the change in AOX amount, they are nonetheless a body of work supporting the idea that this unique respiratory pathway may have a specific role in the photosynthesizing cell (Noguchi and Yoshida ). These finding are further supported by recent computational modelling studies of plant metabolism, some of which predict an increased contribution of AOX to respiration with increasing irradiance (Buckley and Adams , Cheung et al , Nikoloski et al ). Interestingly, a role of AOX in optimizing photosynthesis at high irradiance was also recently established for the diatom Phaeodactylum tricornutum , using an AOX knockdown approach (Bailleul et al ), and knockdown of AOX in soybean has also been shown to perturb photosynthesis (Chai et al ).…”
Section: Introductionsupporting
confidence: 62%
“…Consistent with this, a higher RQ value was observed in soybean leaves under elevated CO 2 (Leakey et al 2009b). Anabolic processes such as nitrate assimilation were also enhanced under elevated CO 2 ; these would contribute to the high RQ, as suggested by the flux-balanced model (Buckley and Adams 2011). Further research should focus on clarifying which anabolic processes are stimulated in shoots under elevated CO 2 .…”
Section: Discussionmentioning
confidence: 79%
“…3). A new analytical model hypothesizing that the oxidative pentose phosphate pathway is progressively inhibited by the light-driven increase in thylakoid reducing power can reproduce the abrupt transition point of the Kok effect (Buckley and Adams, 2011). Direct measurements of R d (with procedures from, for example, Haupt-Herting et al , 2001; Loreto et al , 2001; Pinelli and Loreto, 2003; Pärnik and Keerberg, 2007), combined with a model analysis, might help to understand fully the inter-entangling of the Kok effect, light inhibition of R d , and photorespiration, and to verify the estimates of R d by the indirect methods evaluated in this study.…”
Section: Discussionmentioning
confidence: 99%